The Relationship between Future Time Perspective and Social Support on Career Decision Making Self-Efficacy - Anaresti, Dwi; Sunawan, Sunawan; Awalya, Awalya (Jurnal Bimbingan Konseling, 2022)
Career decision making self-efficacy is greatly needed by students to make the right career decisions. Thus, this study strived for identifying and analyzing the relationship between future time perspective and social support on career decision making self-efficacy. 300 students in Public Senior High School or SMA Negeri throughout West Lampung Regency were involved and selected using cluster random sampling. Their data were collected using future time perspective scale, multidimensional scale of perceived social support, and career decision making self-efficacy scale – short form. Based on the findings, the researchers conclude that there is a positive relationship between future time perspective and career decision making self-efficacy, while social support has nothing to do with it. Further implications and limitations are presented in the discussion chapter.